2015
DOI: 10.1098/rsif.2015.0509
|View full text |Cite
|
Sign up to set email alerts
|

Novel nanocomposite biomaterials with controlled copper/calcium release capability for bone tissue engineering multifunctional scaffolds

Abstract: This work aimed to develop novel composite biomaterials for bone tissue engineering (BTE) made of bioactive glass nanoparticles (Nbg) and alginate cross-linked with Cu 2þ or Ca 2þ (AlgNbgCu, AlgNbgCa, respectively). Twodimensional scaffolds were prepared and the nanocomposite biomaterials were characterized in terms of morphology, mechanical strength, bioactivity, biodegradability, swelling capacity, release profile of the cross-linking cations and angiogenic properties. It was found that both Cu 2þ and Ca 2þ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 79 publications
2
20
0
Order By: Relevance
“…They found that the controlled delivery of Cu ions from borate bioactive glass implants is a promising approach for the healing of bone defects. More studies to utilize nanotechnology to fabricate Cu-containing materials indicated basically similar results that Cu 2+ could promote osteoblast proliferation and accelerate bone fracture healing [ [82] , [83] , [84] , [85] ]. Li et al found that at a concentration of 10 μM lower, Cu 2+ was safe for mouse osteoblastic cell line (MC3T3-E1) and beneficial for its proliferation in a dose-dependent manner.…”
Section: Cu-containing Materials Promoting Bone Fracture Healingmentioning
confidence: 99%
“…They found that the controlled delivery of Cu ions from borate bioactive glass implants is a promising approach for the healing of bone defects. More studies to utilize nanotechnology to fabricate Cu-containing materials indicated basically similar results that Cu 2+ could promote osteoblast proliferation and accelerate bone fracture healing [ [82] , [83] , [84] , [85] ]. Li et al found that at a concentration of 10 μM lower, Cu 2+ was safe for mouse osteoblastic cell line (MC3T3-E1) and beneficial for its proliferation in a dose-dependent manner.…”
Section: Cu-containing Materials Promoting Bone Fracture Healingmentioning
confidence: 99%
“…Together, the different metal ions have functional roles in the physiological cellular environment as well as in the course of bone healing. Thus, the application of metal ions in combination with the above-mentioned bone substitutes or singularly, is of special interest for bone regeneration [ 46 , 47 , 48 ]. To provide an overview of the regenerative potential of the different metal ions, the present review summarizes the knowledge about their involvement in cellular processes and the bone healing process, with a further focus on studies that have already analyzed the regenerative potential of bone substitutes, including metals.…”
Section: Introductionmentioning
confidence: 99%
“…Copper-containing biomaterials, both for hard and soft tissues, have drawn the attention of researchers [ 10 , 11 , 12 , 13 , 14 , 15 ] due to the angiogenetic and antimicrobial properties of copper [ 8 , 9 , 10 , 15 , 16 , 17 ]. The ability to modify the composition of bioactive glasses by introducing therapeutic ions has been exploited to create copper-containing bioactive devices [ 18 ].…”
Section: Introductionmentioning
confidence: 99%